2021
DOI: 10.3390/nu13010151
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Effects of Honeys on Key Biomarkers of Oxidative Stress and Cholesterol Homeostasis in HepG2 Cells

Abstract: Manuka honey and newly developed honeys (arjuna, guggul, jiaogulan and olive) were examined for their physicochemical, biochemical properties and effects on oxidative stress and cholesterol homeostasis in fatty acid-induced HepG2 cells. The honeys exhibited standard moisture content (<20%), electrical conductivity (<0.8 mS/cm), acidic pH, and monosaccharides (>60%), except olive honey (<60% total monosaccharides). They all expressed non-Newtonian behavior and 05 typical regions of the FTIR spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
2
4
0
Order By: Relevance
“…To the best of our knowledge, there are no previously published studies evaluating the effect of thyme and chestnut honeys enriched with royal jelly and propolis on the viability of HepG2 cells. In line with previous results published for individual monofloral honey samples, the concentrations of honeys enriched with royal jelly and propolis resulted in cytotoxicity to HepG2 cells when incubated at 50 mg/mL for more than 24 h [ 31 ]. Nguyen et al (2021) showed that exposure of HepG2 cells to Manuka and other newly developed honeys (arjuna, guggul, jiaogulan, and olive) for 24 h, 48 h, and 72 h significantly reduced cell viability at 50 and 100 mg/mL [ 31 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…To the best of our knowledge, there are no previously published studies evaluating the effect of thyme and chestnut honeys enriched with royal jelly and propolis on the viability of HepG2 cells. In line with previous results published for individual monofloral honey samples, the concentrations of honeys enriched with royal jelly and propolis resulted in cytotoxicity to HepG2 cells when incubated at 50 mg/mL for more than 24 h [ 31 ]. Nguyen et al (2021) showed that exposure of HepG2 cells to Manuka and other newly developed honeys (arjuna, guggul, jiaogulan, and olive) for 24 h, 48 h, and 72 h significantly reduced cell viability at 50 and 100 mg/mL [ 31 ].…”
Section: Resultssupporting
confidence: 91%
“…These authors reported that concentrations up to 50 mg/mL of Manuka honey did not have a significant effect on the viability of HepG2 cells; however, higher concentrations of this type of honey incubated for 48 h had a significant reduction in cell viability [ 30 ]. In addition, a significant decrease in cell viability ( p < 0.05) was observed at 250 mg/mL after treatment with the thyme (42%) and chestnut (30%) samples for 24 h. Recent studies have also evaluated the effect of different honey samples on HepG2 cell viability at similar concentrations and for the same periods of time [ 31 , 32 ]. Halawani (2021) observed a time– and dose–response effect when treating HepG2 cells at 24 h, 48 h, and 72 h with Manuka and Shaoka honeys from Saudi Arabia [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…TPC was evaluated by Folin–Ciocalteu method adopted from Nguyen et al [ 49 ] with some modifications. Briefly, 150 µL of samples were mixed with 750 µL of 10% Folin–Ciocalteu reagent (5 min) and 600 μL of 7.5% Na 2 CO 3 .…”
Section: Methodsmentioning
confidence: 99%
“…The development of the color is also linked to monosaccharide content, which are the sugars that are found in the highest percentage and are responsible for some other sensory and functional properties such as flavor, texture, moisture retention, shelf life, conservation, among others [ 2 ]. Also, the physical and biochemical properties of honey have generated great interest, due to its health-promoting capacity, as well as its anti-inflammatory, antioxidant, antimicrobial, anticarcinogenic, anti-diabetic properties, among others [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%